2018
DOI: 10.3390/ijerph15091832
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Exposure to Perfluoroalkyl Substances and Birth Outcomes; An Updated Analysis from the Danish National Birth Cohort

Abstract: Perfluoroalkyl substances (PFASs) are widespread industrial pollutants that are extremely persistent in the environment. A previous study in the Danish National Birth Cohort (DNBC) found prenatal perfluorooctanoate (PFOA) exposure was associated with decreased birth weight, but had insufficient statistical power to evaluate adverse birth outcomes. Here, we conducted additional analyses in three samples originating from the DNBC for 3535 mothers and infant pairs to evaluate associations between prenatal PFASs e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
83
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(96 citation statements)
references
References 53 publications
10
83
3
Order By: Relevance
“…Outside of the ALSPAC cohort, our weakly inverse or null results are consistent with those reported in other epidemiologic studies of PFAS and birth size. The PFAS concentrations in this study are generally similar to levels reported in previous studies (Apelberg et al, 2007b;Ashley-Martin et al, 2017;Chen et al, 2012;Fei et al, 2007;Hamm et al, 2010;Manzano-Salgado et al, 2017;Meng et al, 2018;Minatoya et al, 2017;Sagiv et al, 2018;Shoaff et al, 2018;Starling et al, 2017;Whitworth et al, 2012;Woods et al, 2017), though PFNA is lowest in the present study. Studies from Japan (n = 168) (Minatoya et al, 2017), the United States (Maryland) (n = 299) (Apelberg et al, 2007b), Denmark (n = 1,400) (Fei et al, 2007), and Taiwan (n = 429) (Chen et al, 2012) have found evidence of inverse associations of PFOA and PFOS with birth size.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Outside of the ALSPAC cohort, our weakly inverse or null results are consistent with those reported in other epidemiologic studies of PFAS and birth size. The PFAS concentrations in this study are generally similar to levels reported in previous studies (Apelberg et al, 2007b;Ashley-Martin et al, 2017;Chen et al, 2012;Fei et al, 2007;Hamm et al, 2010;Manzano-Salgado et al, 2017;Meng et al, 2018;Minatoya et al, 2017;Sagiv et al, 2018;Shoaff et al, 2018;Starling et al, 2017;Whitworth et al, 2012;Woods et al, 2017), though PFNA is lowest in the present study. Studies from Japan (n = 168) (Minatoya et al, 2017), the United States (Maryland) (n = 299) (Apelberg et al, 2007b), Denmark (n = 1,400) (Fei et al, 2007), and Taiwan (n = 429) (Chen et al, 2012) have found evidence of inverse associations of PFOA and PFOS with birth size.…”
Section: Discussionsupporting
confidence: 92%
“…The epidemiological literature on prenatal PFAS exposure and birth size (birth weight, birth length, and head circumference) has been mixed, with some studies finding that higher concentrations are associated with reduced birth size (Apelberg et al, 2007b;Chen et al, 2012;Fei et al, 2007;Maisonet et al, 2012;Meng et al, 2018;Minatoya et al, 2017;Sagiv et al, 2018;Starling et al, 2017), while others observe largely null associations (Ashley-Martin et al, 2017;Hamm et al, 2010;Manzano-Salgado et al, 2017;Shoaff et al, 2018;Whitworth et al, 2012;Woods et al, 2017), with inconsistent results across PFAS chemicals. To date, studies of PFAS exposure and birth size have been conducted in American, Canadian, Danish, Norwegian, Spanish, Japanese, and Taiwanese populations.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we also found significant associations between BW and three additional PFASs (PFNA, PFDA, and PFUnDA). Exposure to these three compounds is substantial, 16,19,20 but they are still much less studied compared with PFOA and PFOS, and previous studies were, with a few exceptions, 11,19,21 small sized. The findings have been inconsistent, [19][20][21][22][23] with indications of slightly lower BW after higher prenatal exposures in only a few studies.…”
Section: Discussionmentioning
confidence: 99%
“…As part of the assessments of the mechanisms behind the effects of PFASs on BW, epidemiological associations of lower BW primarily via shorter pregnancies must also be ruled out. 11 The aim of the present study was therefore to evaluate the association between early pregnancy exposure to eight PFAS compounds and BW in the Swedish Environmental Longitudinal, Mother and child, Asthma and allergy (SELMA) study, specifically focusing on differences according to the sex of the child.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, considerable amounts of PFAS from the mothers can cross the placental barrier and accumulate in the fetus (Fei et al 2007;Manzano-Salgado et al 2015). Numerous epidemiological studies have suggested that prenatal PFAS exposure might affect fetal growth (Bjerregaard-Olesen et al 2019;Fei et al 2008;Liew et al 2018a) and increase risk for preterm birth (Meng et al 2018).…”
Section: Introductionmentioning
confidence: 99%